Three major effects of APOEε4 on Aβ immunotherapy induced ARIA - Foley, Kate E.; Wilcock, Donna M. (Frontiers in Aging Neuroscience, 2024)
The targeting of amyloid-beta (Aβ) plaques therapeutically as one of the primary causes of Alzheimer’s disease (AD) dementia has been an ongoing effort spanning decades. While some antibodies are extremely promising and have been moved out of clinical trials and into the clinic, most of these treatments show similar adverse effects in the form of cerebrovascular damage known as amyloid-related imaging abnormalities (ARIA). The two categories of ARIA are of major concern for patients, families, and prescribing physicians, with ARIA-E presenting as cerebral edema, and ARIA-H as cerebral hemorrhages (micro- and macro-). From preclinical and clinical trials, it has been observed that the greatest genetic risk factor for AD, APOEε4, is also a major risk factor for anti-Aβ immunotherapy-induced ARIA. APOEε4 carriers represent a large population of AD patients, and, therefore, limits the broad adoption of these therapies across the AD population. In this review we detail three hypothesized mechanisms by which APOEε4 influences ARIA risk: (1) reduced cerebrovascular integrity, (2) increased neuroinflammation and immune dysregulation, and (3) elevated levels of CAA. The effects of APOEε4 on ARIA risk is clear, however, the underlying mechanisms require more research.